From Remittances to M-Payments : Understanding 'Alternative' Means of Payment within the Common Framework of Retail Payment System Regulation - World Bank (Washington, DC, 2015)
Retail payment systems play an important role in the smooth functioning of any economy, and thus any inefficiency in the retail payments market can send negative effects cascading throughout the financial realm. The World Bank Global Payment Systems Survey 2010 has shown that inefficiencies persist in the payment systems of many middle-income and low-income countries, with cash continuing to be the most widely used instrument for small-value payments. A number of issues are responsible for this pattern, and the lack of a coherent, holistic strategy for the development of retail payment systems is among the most common. The lessons learned during more than a decade of World Bank Group technical assistance, along with the research findings of other international and national agencies, have been merged into a comprehensive package for the development and reform of the national retail payments system: a) developing a comprehensive national retail payments strategy aims to provide public authorities and market participants with detailed guidance on how to develop and implement a comprehensive, strategic retail payments reform ; b) a practical guide for retail payments stocktaking identifies a methodology for undertaking a detailed stocktaking of a countrys retail payments landscape; c) from remittances to m-payments: Understanding alternative means of payment within the common framework of retail payments system regulation explores the development of a normative framework to underpin an efficient retail payments industry, including the so-called innovative payment mechanisms; and d) innovations in retail payments worldwide: a snapshot: outcomes of the global survey on innovations in retail payments instruments and methods 2010 presents the results of the first World Bank survey among central banks that collected information on innovative retail payment products and programs.